Automatic gate system/ Mohamad Room Marzuki and Ahmad Zahiri Ismail - Marzuki, Mohamad Room; Ismail, Ahmad Zahiri (1991)
A model of an automatic gate system is designed in this project. The system is an electromechanical system which is the combination of a mechanical and electrical system. The electrical system consists of the controller and the motor and the mechanical system includes how the gearing and the rail control the movement of the gate. Three buttons are used to open, stop and close the gate. This system also has a limit switch to stop the gate at the specified distance.